Temporal variations of the two oxygen depleted zones in the Bohai Sea - Wang, Hanzheng; Zhang, Haiyan; Wei, Hao; Zuo, Han (Frontiers in Marine Science, 2023)
The Bohai Sea (BS) has been experiencing prominent deoxygenation in recent years that forms a typically coastal oxygen depleted region in summer. A three-dimensional coupled physical-biogeochemical model was used in this study to investigate temporal variations of the two separately-developing oxygen depleted zones in the BS. Comparison with observations shows a good model performance for multi-year’s oxygen depletion simulation. Two separately-developing oxygen depleted cores are always identified in these years with a threshold of oxygen concentration less than 3 mg/L. The oxygen depletion in the northern core is generally more severe with a larger area and a lower oxygen minima. During the evolution of oxygen depletion, the bottom oxygen concentration decreases more smoothly in the northern core, while fluctuates frequently in the southern core. Nonetheless, the oxygen depletion in both cores fades away almost simultaneously, with a sudden oxygen increase in late summer or early autumn. Oxygen budget estimation indicates that the biological oxygen consumption in the southern core is greater than that in the northern core, but compensated by the oxygen replenishment of oxygen-rich water from the Bohai Strait and vertical diffusion of the water column, which is less in the northern core, so that the oxygen depletion in the northern core is more severe. During oxygen depletion development in June and July, bottom oxygen in the southern core is more susceptible to strong winds than the northern core attributed to differences in topography, with a shallower and smoother bathymetry leading a weaker water column stability in summer. Recognition of characteristics of the two separate oxygen depleted cores would advance understanding spatial pattern of oxygen dynamics and provide a basis for statistical seasonal prediction of coastal oxygen depletion with consideration of spatial heterogeneity.